Assessment centers and the measurement of personality - CHRISTIANSEN, Neil D. (Institutional Knowledge at Singapore Management University, 2013)
Although personality constructs are now widely accepted as being important for understanding work behavior, self-report personality tests as a method of assessment are not without their critics (e.g., Morgeson et al., 2007). Whether misguided or not, concerns persist regarding the validity of these measures and the issue of applicant faking has yet to be fully resolved (Tett & Christiansen, 2007). Moreover, applicant reactions tend to be less favorable for personality inventories than many other assessments commonly used in employment settings (Hausknecht, Day, & Thomas, 2004). To some, self-report inventories may be a poor way to assess personality traits, and yet such inventories are the method most often used to assess these constructs. This trend goes well beyond the area of Industrial and Organizational Psychology. Consistently across the field of psychological measurement, personality is rarely formally assessed by directly observing a person’s behavior (Baumeister, Vohs, & Funder, 2007; for more coverage of personality assessment at work based on observer reports, see Chapter 20, this volume).